On Some Properties of Orthogonal Polynomials over an Area in Domains of the Complex Plane. III - Abdullayev, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study polynomials of higher order orthogonal with weight over domains under the condition that the boundary and weight functions have singularities and do not satisfy the conditions of interference.